Exhaustion of the CD8+ T Cell Compartment in Patients with Mutations in Phosphoinositide 3-Kinase Delta - Wentink, Marjolein W. J.; Mueller, Yvonne M.; Dalm, Virgil A. S. H.; Driessen, Gertjan J.; van Hagen, P. Martin; van Montfrans, Joris M.; van der Burg, Mirjam; Katsikis, Peter D. (Frontiers in Immunology, 2018)
Pathogenic gain-of-function mutations in the gene encoding phosphoinositide 3-kinase delta (PI3Kδ) cause activated PI3Kδ syndrome (APDS), a disease characterized by humoral immunodeficiency, lymphadenopathy, and an inability to control persistent viral infections including Epstein–Barr virus (EBV) and cytomegalovirus (CMV) infections. Understanding the mechanisms leading to impaired immune response is important to optimally treat APDS patients. Immunosenescence of CD8+ T cells was suggested to contribute to APDS pathogenesis. However, the constitutive activation of T cells in APDS may also result in T cell exhaustion. Therefore, we studied exhaustion of the CD8+ T cell compartment in APDS patients and compared them with healthy controls and HIV patients, as a control for exhaustion. The subset distribution of the T cell compartment of APDS patients was comparable with HIV patients with decreased naive CD4+ and CD8+ T cells and increased effector CD8+ T cells. Like in HIV+ patients, expression of activation markers and inhibitory receptors CD160, CD244, and programmed death receptor (PD)-1 on CD8+ T cells was increased in APDS patients, indicating exhaustion. EBV-specific CD8+ T cells from APDS patients exhibited an exhausted phenotype that resembled HIV-specific CD8+ T cells in terms of inhibitory receptor expression. Inhibition of PD-1 on EBV-specific CD8+ T cells from APDS patients enhanced in vitro proliferation and effector cytokine production. Based on these results, we conclude that total and EBV-specific CD8+ T cells from APDS patients are characterized by T cell exhaustion. Furthermore, PD-1 checkpoint inhibition may provide a possible therapeutic approach to support the immune system of APDS patients to control EBV and CMV.